CIReL offers trainings on online teaching and learning - UMP, PNC (2020)
The Centre of Instructional Resources & e‐Learning (CIReL) in collaboration with Human Resource Development Division of Universiti Malaysia Pahang (UMP) organised training programmes on e-learning called Online Education Training. The objective of the programme was to provide better online teaching and learning platform among the lecturers